The development of information and communication technologies: effects on the doctor-patient relationship in Portugal - Alexandre Morais Nunes (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2018)
In recent years, in Portugal, medicine has made great progress with the integration of information technologies at the service of health. However, new technologies have also become part of the routine of patients which are more and more informed about their health problems. This article seeks to identify the impacts of the use of information technologies and of internet on the doctor-patient relationship. For the research, 100 persons (50 doctors and 50 users of the Portuguese public health system) were interviewed. The results showed that despite the technological development and the expansion of the information the doctor-patient relationship is not at risk, because patients continue to trust more their doctor than internet and they believe that although the information systems occupy some minutes of the physician consultation length, they give support to the doctor make his decisions about the diagnosis and the treatment of the patients.